Losing Contact with Nano-object - Binti zulkifli, Safiah (Cranfield University, 2020)
Micro-UAVs of the size of an insect can be used to perform stealthy surveillance or to gather intelligence crucial to attack roles at a relatively short range and within enclosed spaces and buildings. Conventional radar systems have been optimized to detect and classify bigger targets and are not specifically designed to detect micro-targets of less than 5cm in size. Other micro-targets that are relatively small in size are the insect itself. Insect detection have been a great interest too until now, especially those that can cause damage to the agriculture and wide spread of diseases. Early stage of detection help from further massive destruction to happen. Most entomology radars that are being used now are pulsed wave radars whereas FMCW radar offers a better detection in a closer range target which is less than 150 m to the target. The aim of this research is to develop a radar system to detect insect-like UAVs. Ad-hoc detection will be investigated and developed that can offer improved performance.
Keywords: 'FMCW Radar'; 'DSDS19'; 'DSDS19 3MT'; 'Photogrammetry and Remote Sensing'